The Influence of Service Quality on Student Satisfaction in Online Distance Learning Higher Education Based on the E-Quals Model - Sigiyuwanta, Recsatasha (International Journal of Multidisciplinary Research of Higher Education, 2025)
This research is motivated by the importance of service quality in increasing student satisfaction in the Online Distance Learning (ODL) system. The Electronic-Quality for Academic Learning Service (E-QUALS) model is used as a conceptual framework to analyze the various service dimensions that affect student satisfaction levels. The purpose of this study is to empirically examine the effect of service quality dimensions on student satisfaction in the context of higher education at the Open University, Indonesia, which implements Online Distance Learning. The research method used is a quantitative approach with a survey method. The population in this study consisted of 356 Open University students, and a sample of 188 students was selected using random sampling calculated with the Slovin formula with a margin of error of 5%. Data were collected using a questionnaire with a five-point Likert scale and analyzed using the Structural Equation Model method using SmartPLS 4.0. The results showed that e-learning system quality, course content and design, support services, interactivity, and teaching and instructor quality had a significant positive influence on student satisfaction. However, resources and technology infrastructure did not have a significant influence. Overall, this study confirms the importance of Online Distance Learning (ODL) providers to focus on improving technical and non-technical aspects to increase student satisfaction. This study introduces the E-QUALS model as a new approach to measure multidimensional service quality in the context of online distance learning. This model has a significant positive effect on higher education institutions, providing strategic guidance to improve the quality of online distance learning services and its development in various dimensions.